2014
DOI: 10.5897/ajps12.158
|View full text |Cite
|
Sign up to set email alerts
|

Survival, growth and biomass production of Moringa oleifera provenances at Gairo inland plateau and Ruvu Coastal Region in Tanzania

Abstract: Survival, growth and biomass production was studied among 14 Moringa oleifera provenances at Gairo inland plateau-Morogoro, and Ruvu Coastal Region in Tanzania employing randomized complete block design with three replications. Growth assessment was done at six months intervals while biomass assessment was only done at 30 months. During final assessment, untransformed survival at Gairo site ranged from 65.33% for Chikwawa/Domasi (Malawi) to 98.67% for Ihumwa (Tanzania) while at Ruvu site, it ranged from 92% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…Based on table 1, provenance had no significant effect on the life percentage of kelor seedling, either at 1 MAS or 3 MAS. This condition is different from the result of research by Ezekiel et al [12], which showed significant survival differences in 14 different provenances.…”
Section: Life Percentagecontrasting
confidence: 87%
“…Based on table 1, provenance had no significant effect on the life percentage of kelor seedling, either at 1 MAS or 3 MAS. This condition is different from the result of research by Ezekiel et al [12], which showed significant survival differences in 14 different provenances.…”
Section: Life Percentagecontrasting
confidence: 87%
“…The tree is of a wide, open, and classically umbrella-shaped crown and often just a single stem, usually taking roots deep down. 12 The leaves of moringa have alternate phyllotaxy, with each large leaf being about 90 cm long and being spacing almost 5 cm apart on the mid stalk. Leaflets are coloured dark green when viewed from above and pale green when viewed from beneath.…”
Section: Methodsmentioning
confidence: 99%
“…The shoots and twigs and usually short, though thickly hairy. The tree is of a wide, open, and classically umbrella‐shaped crown and often just a single stem, usually taking roots deep down 12 . The leaves of moringa have alternate phyllotaxy, with each large leaf being about 90 cm long and being spacing almost 5 cm apart on the mid stalk.…”
Section: Botanical Details Of M Oleiferamentioning
confidence: 99%
See 1 more Smart Citation
“…Even though it is not indigenous to Tanzania, it is increasingly becoming a popular plant for medicinal and nutritional value. See Ezekial et al, 2014. a shelf to keep the bucket of water, and it would be enclosed by a wooden fence made from bamboo. "I was going to put in a new shower here, but my daughter decided to continue her studies in Mwanza city, so now I will pay for that.…”
Section: Using Flour To Offset Uncertainties In Farmingmentioning
confidence: 99%